2016
DOI: 10.1007/s10815-016-0663-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on the male reproductive system

Abstract: The study aims to discuss the effects of aging on the male reproductive system. A systematic review was performed using PubMed from 1980 to 2014. Aging is a natural process comprising of irreversible changes due to a myriad of endogenous and environmental factors at the level of all organs and systems. In modern life, as more couples choose to postpone having a child due to various socioeconomic reasons, research for understanding the effects of aging on the reproductive system has gained an increased importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(150 citation statements)
references
References 146 publications
(162 reference statements)
9
134
1
6
Order By: Relevance
“…When either starved or amputated, the hermaphroditic sexual organs are resorbed likely due to loss of nhr-1 signaling, only to be restored once food is available, the animals reach an appropriate size (Newmark and Sanchez Alvarado, 2002), and lipid metabolism is once again activated to maintain the RS. In both men and women, the reduction of hormone synthesis and gametes are usually the earliest signs of aging (Gunes et al, 2016; Makabe et al, 1998), with other organs such as the liver and brain decreasing in volume in the elderly (Hedman et al, 2012; Makabe et al, 1998; Motta et al, 2002; Paniagua et al, 1991; Tajiri and Shimizu, 2013). Moreover, the ectopic lipid accumulation observed in normal aged people and premature menopause patients (Knauff et al, 2008; Toth and Tchernof, 2000), is only observed in planarians after the loss of either nhr-1 or acs-1 .…”
Section: Discussionmentioning
confidence: 99%
“…When either starved or amputated, the hermaphroditic sexual organs are resorbed likely due to loss of nhr-1 signaling, only to be restored once food is available, the animals reach an appropriate size (Newmark and Sanchez Alvarado, 2002), and lipid metabolism is once again activated to maintain the RS. In both men and women, the reduction of hormone synthesis and gametes are usually the earliest signs of aging (Gunes et al, 2016; Makabe et al, 1998), with other organs such as the liver and brain decreasing in volume in the elderly (Hedman et al, 2012; Makabe et al, 1998; Motta et al, 2002; Paniagua et al, 1991; Tajiri and Shimizu, 2013). Moreover, the ectopic lipid accumulation observed in normal aged people and premature menopause patients (Knauff et al, 2008; Toth and Tchernof, 2000), is only observed in planarians after the loss of either nhr-1 or acs-1 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning reproduction, increasing male age was associated with two major risk factors: first, decline in fertility and second, health impairments of children fathered by men of advanced age (Sharma et al ., ; Gromoll et al ., ). The suggested age‐associated decline in fertility was attributed to decreased sperm parameters, for example sperm counts and sperm motility (Eskenazi et al ., ; Kühnert & Nieschlag, ; Begueria et al ., ; Gunes et al ., ). Additional data for declining germ cell numbers and testicular ageing were provided by Holstein et al .…”
Section: Introductionmentioning
confidence: 97%
“…Because of this deterioration, hormone production and spermatogenesis changes with too. As a result, these changes in spermatozoa increase with ageing (Gunes, Hekim, Arslan, & Asci, ).…”
Section: Discussionmentioning
confidence: 99%